Performance Aggregation and Decentralized Contracting - Feltham, Gerald A.; Hofmann, Christian; Indjejikian, Raffi J. (The Accounting Review, 2016)
ABSTRACT We examine how accounting practices that aggregate or disaggregate the contributions of different economic agents influence the choice of organizational form. We consider a principal/multi-agent model where the principal either contracts with all parties directly or delegates part of the contracting authority to one of the agents. Delegated contracts improve risk sharing and generate implicit incentives for the agent entrusted with contracting authority. However, delegated contracts also entail a loss of control in motivating lower-level agents. In addition, when performance is aggregated, delegated contracts render agents' incentives more interdependent and create spillovers up and down the hierarchy. We demonstrate that accounting practices that aggregate the performance of multiple agents can complement organizational forms characterized by greater decentralization. In contrast, accounting practices that capture agents' performance contributions separately favor more centralized organizational forms. Our findings suggest that in settings where performance measurement systems are more aggregate, decentralization is more prevalent. JEL Classifications: L22; M12; M4.